(3eaQL GdfaSs - (3eLO GdOjf YHO GdhgGH Hf SMfhf GdJfhNj,J (B694 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg NGdb GdOGA hGdOhGA , GdefbP ef GdCYGQV hGdCOhGA , HeaQMGJ GdfLGI hGdTaGA aEfi deG GWdYJ Ydi CcKQ GdcJH GdWHjI ade CLO ajgG eG jTai GdbdH ai PcQ GdCehQ GdeaQMI ddfaS s
(3BNQgG (B:s
(3hdMUhd eG jMJGLg hjghGg ef Ci Ufa cGf ef GdehLhOGJ aHPGc Cced GdeaQMGJ s
(3HYV GdcdeGJ cJHJ HGdMeQI ade JXgQ ai GdJUhjQs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B240 s
Keywords: (3GdWHs